What the moon said - Rosengren, Gayle (New York : G. P. Putnam's Sons, an imprint of Penguin Group (USA), 2014)
When Esther's family moves to a farm during the Great Depression, she soon learns that there are things much more important than that her superstitious mother rarely shows her any affection.
Keywords: Farm life -- Wisconsin -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Superstition -- Juvenile fiction; Families -- Wisconsin -- Juvenile fiction; Depressions -- 1929 -- Juvenile fiction; Wisconsin -- History -- 20th century -- Juvenile fiction; Farm life -- Wisconsin -- Fiction; Mothers and daughters -- Fiction; Superstition -- Fiction; Family life -- Wisconsin -- Fiction; Depressions -- 1929 -- Fiction; Wisconsin -- History -- 20th century -- Fiction